Effects of carbazole‐degradative plasmid pCAR1 on biofilm morphology in Pseudomonas putida KT2440. Issue 2 (28th January 2016) - Lee, Seunguk; Takahashi, Yurika; Oura, Hiromu; Suzuki‐Minakuchi, Chiho; Okada, Kazunori; Yamane, Hisakazu; Nomura, Nobuhiko; Nojiri, Hideaki
Summary: Bacteria typically form biofilms under natural conditions. To elucidate the effect of the carriage of carbazole‐degradative plasmid pCAR1 on biofilm formation by host bacteria, we compared the biofilm morphology, using confocal laser scanning microscopy, of three pCAR1‐free and pCAR1‐carrying P seudomonas hosts: P . putida  KT2440, P . aeruginosa  PAO1 and P . fluorescens  Pf0–1. Although pCAR1 did not significantly affect biofilm formation by PAO1 or Pf0–1, pCAR1‐carrying KT2440 became filamentous and formed flat biofilms, whereas pCAR1‐free KT2440 formed mushroom‐like biofilms. pCAR1 contains three genes encoding nucleoid‐associated proteins (NAPs), namely, Pmr, Pnd and Phu. The enhanced filamentous morphology was observed in two double mutants [KT2440(pCAR1Δ pmr Δ pnd ) and KT2440(pCAR1Δ pmr Δ phu )], suggesting that these NAPs are involved in modulating the filamentous phenotype. Transcriptome analyses of the double mutants identified 32 candidate genes that may be involved in filamentation of KT2440. Overexpression of PP_2193 in KT2440 induced filamentation and overexpression of PP_0308 or PP_0309 in KT2440(pCAR1) enhanced filamentation of cells over time. This suggests that pCAR1 induces development of an abnormal filamentous morphology by KT2440 via a process involving overexpression of several genes, such as PP_2193. In addition, pCAR1‐encoded NAPs partly suppress too much filamentation of KT2440(pCAR1) by repressing transcription of some genes, such as PP_0308 and PP_0309.